THE PERSONALITY MODEL OF THE MODERN TEACHER AND HER FORMATION IN THE CONDITIONS OF HIGHER SCHOOL (Pedagogy of Higher and Secondary Education, 2007)
The paper deaals witv the grounding of the structural pattern of modern teacher personality as well as the conditious of its successful realisation in higher school educational process.